An operational workflow for documenting and communicating architectural heritage: from survey to 3D printing - Adriana Marra; Luca Vespasiano (Disegnare con)
Digital surveying and rapid prototyping techniques are important tools to support processes related to cultural and architectural heritage. Digital surveying can be used to document, analyse, and enjoy the built heritage thanks to point clouds and detailed digital models resulting from the processing of data acquired during field activities. 3D printing, on the other hand, enables the creation of realistic physical replicas of heritage artefacts that can support activities related to analysis, documentation, conservation, valorisation and enjoyment. The use and combination of these techniques to architectural and cultural heritage have brought benefits and advantages since digital and physical replicas can be used in the processes of documenting, analysing, preserving and enhancing historical artefacts by promoting their accessibility on multiple levels. The paper discusses the results of research aimed at defining and testing an effective workflow for the development of physical models suitable for the analysis, documentation and communication of architectural heritage. The experimentation was performed considering as a case study a peculiar element of architecture, a historical portal. The paper illustrates the technical challenges faced starting from the photogrammetric survey to the digital reconstruction of the analysed artefact for 3D printing, with a focus on the printing parameter settings used to produce physical replicas with high-quality, but different resolutions and scales, to be used for several purposes, such as analysis and documentation and education and communication. DOI: https://doi.org/10.20365/disegnarecon.31.2023.18